Kajian Dampak Pandemi Covid-19 Terhadap Perekonomian Di Kabupaten Ende Dan Strategi Pemulihannya - Ernesta Leha; yustina paulina penu; yohanes pande; mansyur abdul hamid (Magister Manajemen STIE Bank BPD Jateng, 2022)
The weakening of national economic conditions due to the Covid-19 pandemic has an impact on economic conditions in the regions, including in Ende Regency. Restrictions on community activities have disrupted economic activity in all sectors, including the Micro, Small and Medium Enterprises (MSME) sector. This can be seen in the reduced trading activity at several market in Ende Regency. This study was conducted to find out how much impact the Covid-19 pandemic had on the economy in Ende Regency. The results showed that (1) the economic condition in Ende Regency prior to the Covid-19 Pandemic was sufficiently demonstrated by the low GRDP value of Ende Regency; (2) The Direct Cash Assistance (DCA) policy has an economic impact on the community but it is not yet very effective because there are still many people who do not receive DCA funds even though they meet the criteria as prospective DCA recipients; (3) The impact of the Covid-19 Pandemic on the community is experienced by business actors more than farmers and the biggest impact is on the decline in the income level of MSME actors; (4) Ende Regency's economic sustainability is in a less sustainable status in terms of economic, social and institutional aspects; (5) The dominant variables affecting the economic status of Ende Regency are (1) superior products and limited online marketing; (2) public understanding of the governance that occurs and (3) there is no marketing agency in Ende Regency.